O01.6 Persistent SIV-Seronegative Macaque Monkeys Generate Multi-Cytokine Anti- SIV Mucosal Immune Responses Following Serial Low-Dose SIV Mucosal Challenge. (13th July 2013) - MacDonald, K S; Haq, K; Chan, J; Iwajomo, O; Janes, M; Perciani, C; Pilon, R; Caldwell, D; Sandstrom, P; Willer, D O
Abstract : Background: There are no systematic prospective human or simian studies on the effects of repeated sub-infectious doses of HIV/SIV on mucosal and systemic immunity. The capacity and mechanism of how these responses may impact acquisition and subsequent disease course are also unknown. Methods: To address this, we examined cynolmolgus macaques as part of a vaccine trial, for their ability to generate mucosal and systemic immune responses following repeated ultra low-dose mucosal SIVmac239 challenge. Animals were challenged intra-rectally weekly according to a 24-week dose-escalation. Blood was obtained weekly, and rectal biopsies were obtained 18 to 24w post SIV challenge and analysed by flow cytometry for anti-SIV T-cell responses. Intracellular cytokine responses (IFN-γ, IL-2, TNFα and CD107a) were measured. Results: Total CD4+ responses against two distinct antigenic targets correlated with apparent resistance to infection as measured by the number of challenges, total dose and infecting dose. Moreover, CD8+ responses were also predictive of susceptibility to infection. Both CD4 and CD8 T cell effectors were observed secreting IFN γ, TNF α, IL2 and CD107a in response to SIV gene products not present in the SIV vaccine that the animals received. Placebo-vaccinated animals did not have significantly fewer mucosal immune responses than vaccinees but they did have fewer blood responses suggesting that mucosal responses were generated by the SIV exposure while systemic responses were generated by the vaccine. Multiple sub-infectious SIV challenges did not induce humoral responses in the blood, as determined by western blot assay. Conclusions: Together, this data suggests that these mucosal immune responses are the predominantly the result of priming by repeated low dose SIV challenge. Such an effect alters subsequent susceptibility to infection which has implications for vaccine studies and for understanding the biology of transmission since it increases the resistance to infection of both vaccinees and placebo recipients unpredictably.